APLIKASI SISTEM PENGELOLAAN ATK (ALAT TULIS KANTOR) AKADEMI ANGKATAN UDARA YOGYAKARTA - Deny Wiria Nugraha; Imat Rahmat Hidayat (Jurusan Teknik Informatika, 2011)
Information Systems is an essential requirement for every company or government agency. Included in the Air Force Academy in Yogyakarta, information systems becomes an important component in the system run. Among them is the Stationery Office Management System that has a very high complexity.ATK management system requirements in the Air Force Academy Yogyakarta is needed. Because the extent of management systems that run. So management needs ATK becomes very important. Due to a very large nominal amount if calculated in the long term in accordance with the procurement conducted. This is to reduce errors in the recording which was done manually. Development method makes the system using the waterfall is running ssuai sisem needs. So the rate of change and improvement that occurred in the system will run continuously.